The Effect of Using Oral Probiotics on Dental and Oral Health in Type 2 Diabetes Mellitus Patients at Dr. M. Djamil General Hospital, Padang, Indonesia - Farhanah, Farhanah (Crown: Journal of Dentistry and Health Research, 2024)
Introduction: Type 2 diabetes mellitus (T2DM) can increase the risk of periodontal disease and oral infections. Oral probiotics are believed to help maintain healthy teeth and mouth in T2DM patients. This study aims to evaluate the effect of using oral probiotics on dental and oral health in T2DM patients at Dr. M. Djamil General Hospital Padang. Methods: A total of 60 T2DM patients were randomly divided into two groups: the probiotic group (n=30) who received oral probiotic supplements for 12 weeks and the control group (n=30) who received a placebo. Plaque index, gingival index, and periodontal pocket depth were measured at the beginning and end of the study. Results: In the probiotic group, there was a significant reduction in plaque index (p=0.001) and gingival index (p=0.002) compared to the control group. Periodontal pocket depth also showed a significant decrease in the probiotic group (p=0.005). Conclusion: The use of oral probiotics for 12 weeks can improve dental and oral health in T2DM patients by reducing plaque index, gingival index, and periodontal pocket depth.